Big conductance calcium‐activated potassium channel openers control spasticity without sedation. (7th July 2017) - Baker, David; Pryce, Gareth; Visintin, Cristina; Sisay, Sofia; Bondarenko, Alexander I; Vanessa Ho, W S; Jackson, Samuel J; Williams, Thomas E; Al‐Izki, Sarah; Sevastou, Ioanna; Okuyama, Masahiro; Graier, Wolfgang F; et al.
Abstract : Background and Purpose: Our initial aim was to generate cannabinoid agents that control spasticity, occurring as a consequence of multiple sclerosis (MS), whilst avoiding the sedative side effects associated with cannabis. VSN16R was synthesized as an anandamide (endocannabinoid) analogue in an anti‐metabolite approach to identify drugs that target spasticity. Experimental Approach: Following the initial chemistry, a variety of biochemical, pharmacological and electrophysiological approaches, using isolated cells, tissue‐based assays and in vivo animal models, were used to demonstrate the activity, efficacy, pharmacokinetics and mechanism of action of VSN16R. Toxicological and safety studies were performed in animals and humans. Key Results: VSN16R had nanomolar activity in tissue‐based, functional assays and dose‐dependently inhibited spasticity in a mouse experimental encephalomyelitis model of MS. This effect occurred with over 1000‐fold therapeutic window, without affecting normal muscle tone. Efficacy was achieved at plasma levels that are feasible and safe in humans. VSN16R did not bind to known CB1 /CB2 /GPPR55 cannabinoid‐related receptors in receptor‐based assays but acted on a vascular cannabinoid target. This was identified as the major neuronal form of the big conductance, calcium‐activated potassium (BKCa ) channel. Drug‐induced opening of neuronal BKCa channels induced membrane hyperpolarization, limiting excessive neural‐excitability and controlling spasticity. Conclusions and Implications: We identified the neuronal form of the BKCa channel as the target for VSN16R and demonstrated that its activation alleviates neuronal excitability and spasticity in an experimental model of MS, revealing a novel mechanism to control spasticity. VSN16R is a potential, safe and selective ligand for controlling neural hyper‐excitability in spasticity.